Effect of two insect pests on Acacia auriculiformis tree growth and form in Australia's Northern Territory - Montagu, K. D. (2017)
The occurrence and damage caused by two insect pests of Acacia auriculiformis was assessed four months after planting in two clonal seed orchards containing trees from the Queensland, Papua New Guinea and Northern Territory provenances. The effect of insect damage on tree growth and form was subsequently measured over a 16-month period. Four months after planting, when the trees averaged 1.3m in height, the insects Platymopsis humeralis F. (Coleoptera, Cerambycidae) and Mictis profana F. (Hemiptera, Coreidae) were present on 8 and 36% of the trees respectively. However, both the insects caused damage to more than 50% of the trees at the two sites. Platymopsis humeralis girdled the main stem of the juvenile trees which reduced tree height growth by 0.4—0.5 m in the six months following girdling. Mictis profana caused the death of 10-15% of the tree shoot tips, but this had no measurable effect on tree growth. No provenance variation was observed in either the degree of insect attack or effect on tree growth or form. Twenty months after planting there was no apparent effect on tree form and no further reduction in tree height growth.